Fannidae and Muscidae (Diptera) from Nicaragua - Shigeo, S.=700 1 Schnell, G.; Barros de Carvalho, J.B.
(Es, En)
Ilus., 29 ref
Keywords: FANNIDAE; MUSCIDAE; INSECTA; ARTHROPODA; TAXONOMIA; DISTRIBUCION GEOGRAFICA; REGION NEOTROPICAL; AMERICA CENTRAL; NICARAGUA; REVISTA NICARAGUENSE DE ENTOMOLOGIA